Pengembangan Multimedia Interaktif Berbasis Adobe Flash Pada Mata Pelajaran Bimbingan TIK Kelas VIII SMP - sesmiati; Zuliarni (Journal of Pedagogy and Online Learning, 2022)
The development of interactive multimedia is carried out as an effort to solve student learning problems, where the limited number of hours of lessons at school, practical material, the risk of students being left behind is greater, causing disturbances in the classroom such as students often making noise and sometimes disturbing their friends. This is also caused by the limited existing learning media, the lack of teacher variation utilizing educational media, both conventional and technology-based media. This study uses the Research and Development (RnD) research method, using the Borg and Gall development model. The development procedure in this study is procedural and simplified according to the needs of the researcher, namely (1) data collection, (2) product design, (3) product development, (4) validation and revision, (5) product trial, (6) product end. Product validity was carried out by 3 people, namely 2 media validators and 1 material validator, while the number of research subjects was 24 students of SMP Negeri 1 Ampek Angkek. The data collection instrument is in the form of a questionnaire, assessment formats and test questions. Data were analyzed descriptively qualitatively and quantitatively. Based on the results of the feasibility assessment of the media validator and material validator, it can be concluded that the results of the assessment by two media experts are categorized as "Very Valid" for use with the number of assessments from validator I getting an average of 4.96 and validator II an average of 5.00. While the results of the material expert's assessment were categorized as "Very Valid" with an average of 4.44. The results of the interactive multimedia practicality test are in the "Practical" category with an average rating of 4.37. The results of the effectiveness test show that t_count > from t_table so that it shows a significantly higher difference between pretest and posttest. Based on the results of the validity test, practicality test and effectiveness test, it can be stated that this interactive multimedia based on Adobe Flash CS6 is suitable for use in learning.